Pemeliharaan Lobster Pasir (Panulirus Homarus) Menggunakan Keramba Jaring Dasar Di Perairan Selat Bali - Ulkhaq, Mohammad Faizal; Efendi, Irzal (Universitas Madako Tolitoli, 2025)
Spiny lobster (Panulirus homarus) is one of the marine commodities that has a high demand value and export commodities to Singapore, Hong Kong, China, Japan, Thailand, Malaysia, Vietnam and Korea. However, most of the spiny lobster still comes from natural catches which these productivity is decreasing. Therefore, spiny lobster farming one of strategies to fulfil the high demand for lobster and maintain the spiny lobster population in nature. Spiny lobster cultivation technology can be carried out in floating net cages, fixed net cages and bottom/sinking net cages. The bottom cage system was to be the best methods because it can prevent cultured organisms from predators, temperature fluctuations and surface pollutants such as trash and oil spills. The objective of this study is to evaluate the spiny lobster culture system using bottom net cages, especially in the Bali Strait Waters. This research was conducted from 9 August - 9 October 2021 at the Bottom Net Cage System Lobster Cultivation Pilot Unit, ‘PESONA BAHARI’ Banyuwangi, East Java. The method used in this research is descriptive explorative and comparative through primary and secondary data collection. Parameters observed included specific growth rate, feed conversion ratio and survival rate. The data obtained were then descriptively analysed using table. The results showed that the sand lobster culture system with round bottom net cages in the Bali Strait Waters showed higher SGR, FCR and SR values than the box shape.